The use of diaphragmatic flap for the main bronchus stump reinforcement in right-sided pneumonectomy performed for destructive pulmonary tuberculosis with drug resistance of Mycobacterium tuberculosis - A. O. Avetisyan; I. S. Serezvin; G. G. Kudriashov; A. V. Chausov; E. A. Davydenkova; O. P. Sokolova; V. F. Li; K. A. Stashkova; P. K. Yablonskii (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. Drug-resistant tuberculosis with subtotal and total lesion of one of the lungs is the most common indication for pneumonectomy. This operation is accompanied by a high risk of postoperative complications, among which the most dangerous is pleural empyema with bronchopleural fistula. In this regard, the prevention of this complication is an extremely important task.The OBJECTIVE was to study the results of using a diaphragmatic flap to prevent the development of right main bronchus stump insufficiency with bronchopleural fistula in patients with destructive pulmonary tuberculosis. METHODS AND MATERIALS. A retrospective study was carried out for the period from 2015 to 2019. The study included 13 patients who underwent right-sided pneumonectomy with diaphragmoplasty of the right main bronchus stump. Indications for diaphragmoplasty were: persistent bacterial excretion at the time of surgery, pre-existing bronchopleural fistula, intraoperative pleural contamination, progressive course of a specific process.RESULTS. The postoperative period was smooth in 10 (77 %) patients. Postoperative complications developed in 3 (23 %) patients: in 1 (7.7 %) case, there was right main bronchus stump insufficiency with bronchopleural fistula and in 2 (15.3 %) cases, there were right main bronchus stump insufficiency without bronchopleural fistula. A satisfactory immediate result was achieved in 12 (92.3 %) patients.CONCLUSION. The diaphragmatic flap is a reliable material for plasty of the right main bronchus stump in order to prevent the formation of bronchopleural fistula in destructive pulmonary tuberculosis.